Primary epiphyseal ewing sarcoma: A case report - Bülbül, Murat; Özger, Harzem; Bilgiç, Bilge; Eralp, Levent (Turkish Society of Orthopaedics and Traumatology, 2012)
Ewing sarcoma is a frequently seen malignant bone tumor of the childhood. The tumor involves the diaphyseal and metaphyseal bone and cases located in the epiphysis are unusual. We present a case of Ewing sarcoma limited to the epiphysis in an immature skeleton. We would like to emphasize the importance of the biopsy without contaminating the joint space which will reduce the morbidity during the curative surgery.

Çocukluk çağı tümörlerinden Ewing sarkomu sık görülen, habis bir kemik patolojisidir. Diyafizer ve metafizer kemiklerde lokalize olan tümörün epifizde yerleşimi alışılmış değildir. Bu yazıda, iskelet olgunlaşmasını tamamlamamış bir hastada epifizde sınırlanmış Ewing sarkomu olgusunu sunuyoruz. Eklemi kontamine etmeden gerçekleştirilecek biyopsinin küratif cerrahi sırasında morbiditeyi azaltmadaki etkisine dikkat çekmek isteriz.
Primer epifiz lokalizasyonlu Ewing sarkomu: Olgu sunumu
Keywords: Bone tumors; Epiphysis; Ewing sarcoma; Epifiz; Ewing Sarkomu; Kemik Tümörleri